2023
DOI: 10.3389/fneur.2023.1214814
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of psychiatric features of traumatic encephalopathy syndrome as conceptualized in the 20th century

Abstract: IntroductionSome ultra-high exposure boxers from the 20th century suffered from neurological problems characterized by slurred speech, personality changes (e.g., childishness or aggressiveness), and frank gait and coordination problems, with some noted to have progressive Parkinsonian-like signs. Varying degrees of cognitive impairment were also described, with some experiencing moderate to severe dementia. The onset of the neurological problems often began while they were young men and still actively fighting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…A recent review of this same case material, including 155 of these 157 boxers from the 20 th century, was focused on whether these men exhibited psychiatric problems, such as depression, anxiety, and suicidality. 15 That review concluded that TES during the 20 th century was described as a neurological condition, including dementia in some cases, and depression, anxiety, and suicidality were not considered to be core clinical features—supporting the decision of the 2021 TES consensus group 20 removing depression from the 2014 preliminary diagnostic criteria 11 for TES. For the present study, we extracted information from these same 155 cases (with two additional identified cases) presented in 21 articles 1 , 2 , 5–7 , 27 , 28 , 30–32 , 34 , 35 , 37–44 , 46 and applied the 2021 TES consensus diagnostic criteria for the three core clinical features (i.e., progressive course, cognitive impairment, and/or neurobehavioral dysregulation), in addition to the supportive features, including whether there was a delayed onset of symptoms, motor signs, or psychiatric features (see the Supplementary Material ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of this same case material, including 155 of these 157 boxers from the 20 th century, was focused on whether these men exhibited psychiatric problems, such as depression, anxiety, and suicidality. 15 That review concluded that TES during the 20 th century was described as a neurological condition, including dementia in some cases, and depression, anxiety, and suicidality were not considered to be core clinical features—supporting the decision of the 2021 TES consensus group 20 removing depression from the 2014 preliminary diagnostic criteria 11 for TES. For the present study, we extracted information from these same 155 cases (with two additional identified cases) presented in 21 articles 1 , 2 , 5–7 , 27 , 28 , 30–32 , 34 , 35 , 37–44 , 46 and applied the 2021 TES consensus diagnostic criteria for the three core clinical features (i.e., progressive course, cognitive impairment, and/or neurobehavioral dysregulation), in addition to the supportive features, including whether there was a delayed onset of symptoms, motor signs, or psychiatric features (see the Supplementary Material ).…”
Section: Methodsmentioning
confidence: 99%
“…These criteria included cognitive impairment and neurological problems, but also diverse psychiatric and psychosocial problems, such as depression, intermittent explosive disorder, anxiety (e.g., obsessive-compulsive disorder and generalized anxiety disorder), excessive gambling, excessive shopping, substance abuse, suicidality, and paranoia. The diverse psychiatric problems that defined the 2014 TES core and supportive diagnostic criteria, however, were not considered part of the clinical syndrome experienced by boxers in the 20th century 15 —and researchers have illustrated the risk of misdiagnosing TES in persons from the general population based on considering the possible psychiatric features. 16–19 …”
Section: Introductionmentioning
confidence: 99%
“…Fast-forward almost a hundred years and RHI through American football participation receives a large share of the spotlight. Parkinsonism remains a recognized symptom in a subset of individuals often decades removed from their RHI exposure, albeit not as consistently reported as in the days of “dementia pugilistica.”…”
mentioning
confidence: 99%
“…Parkinsonism remains a recognized symptom in a subset of individuals often decades removed from their RHI exposure, albeit not as consistently reported as in the days of "dementia pugilistica." 7 Historical case reports did not have the benefit of clinicopathological correlation of parkinsonism in individuals with RHI. While the unusual symptom constellations were readily apparent both to observant medical professionals and the keen eyes of boxing fans in the crowd, 4 the underlying cause was not.…”
mentioning
confidence: 99%